The priest in love. A comparative study of Matthew Lewis' "The Monk" and Clarín's "La Regenta" - Romero Jódar, Andrés (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
Matthew Lewis’s The Monk and Clarín’s La Regenta share a great deal of similarities. Both novels belong to a context of end of the century –although theirs are different fin-de-siècles–, and show a common sensibility at dealing with topics such as religion, or the treatment of the figure of the priest. This essay aims to highlight and analyze some of those shares features, especially centring on the topic theme of the priest in love as the nuclear character in both novels. The Monk may be said to be an important thematic antecedent for La Regenta –but not necessarily an intertextual source in its elaboration–. The repetition of situations and themes, as it also happens in El crimen del padre Amaro, will help us draw a common argumentative line, placing these works in a general frame that evolves –or not– throughout the history of literature.